Changes in the relationship between sprint and horizontal jump performance according to sprint levels in children and adolescents - Mello, J. B.; Preissler, A. A. B.; Schons, P.; Ojeda-Aravena, A.; Hurtado, J.; Paez, J.; Gaya, A. (International Journal of Performance Analysis in Sport, 2024)
The aim of this research was to determine the relationship between horizontal jump performance and sprint performance according with the sprint levels of children and adolescents. This study is a cross-sectional analysis from PROESP-Br database with 77,384 children and adolescents with an age range of 6-18 years. We use data about the horizontal jump test and 20-m sprint test (the covariables were age, height, body mass, arm-span and maturity offset). The sprint was classified using percentiles, the coefficient of determination (R2), ß values, and p-value <0.05 were calculated (sprint as dependent and horizontal jump performance as independent) in each category. We identify a significant correlation between horizontal jump performance and sprint (R2 cubic for boys: 0.265; R2 cubic for girls: 0.204). For girls and boys, the greater R2 was identified in the regular (P40-60), good (P60-80), and very good (P80-98) categories. For these three categories, each centimetre more in the horizontal jump was a reduction of between 0.005 and 0.007 s in the 20-m sprint test. The results demonstrate that children and adolescents with extreme levels of sprinting (very slow or very fast) have a sprint performance that is not related to horizontal jump performance, independent of anthropometric factors, age, and maturity offset.